The Effect of Work Motivation and Work Discipline on Employee Performance with Job Satisfaction as a Mediating Variable in the Welfare Division of the Regional Secretariat of Manokwari District - WIBOWO, Noviardi Angga; SARA, I Made; PUTRA, Ida Bagus Udayana (International Journal of Environmental, Sustainability, and Social Science, 2025)
Human Resources (HR) is a key asset in driving organizational success across sectors. Improving HR quality is essential for enhancing employee performance, which reflects an individual’s ability to meet work targets effectively and sustainably through competence, responsibility, adaptability, and contributions to organizational goals. This study aims to examine the influence of work motivation and work discipline on employee performance, with job satisfaction as a mediating variable in the People’s Welfare (Kesra) Section of the Manokwari Regency Regional Secretariat. The research involved 32 honorary employees, using a saturated sampling method. Data were collected through questionnaires and analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS). The results show that work motivation positively and significantly affects both job satisfaction and employee performance. Work discipline positively affects performance, though the effect is not significant, while it significantly affects job satisfaction. Job satisfaction significantly impacts employee performance and partially mediates the relationship between work motivation and performance, but not between work discipline and performance. To enhance performance in the Kesra Section, efforts should focus on boosting motivation and discipline through recognition programs, training, and consistent rule enforcement. Additionally, fostering a supportive work environment is crucial, given job satisfaction’s mediating role in improving performance outcomes. These strategies can lead to sustainable improvements in employee performance